Habenular connections with the dopaminergic and serotonergic system and their role in stress‐related psychiatric disorders. (27th December 2019) - Metzger, Martin; Souza, Rudieri; Lima, Leandro B.; Bueno, Debora; Gonçalves, Luciano; Sego, Chemutai; Donato, Jose; Shammah‐Lagnado, Sara J.
Abstract: The habenula (Hb) is a phylogenetically old epithalamic structure differentiated into two nuclear complexes, the medial (MHb) and lateral habenula (LHb). After decades of search for a great unifying function, interest in the Hb resurged when it was demonstrated that LHb plays a major role in the encoding of aversive stimuli ranging from noxious stimuli to the loss of predicted rewards. Consistent with a role as an anti‐reward center, aberrant LHb activity has now been identified as a key factor in the pathogenesis of major depressive disorder. Moreover, both MHb and LHb emerged as new players in the reward circuitry by primarily mediating the aversive properties of distinct drugs of abuse. Anatomically, the Hb serves as a bridge that links basal forebrain structures with monoaminergic nuclei in the mid‐ and hindbrain. So far, research on Hb has focused on the role of the LHb in regulating midbrain dopamine release. However, LHb/MHb are also interconnected with the dorsal (DR) and median (MnR) raphe nucleus. Hence, it is conceivable that some of the habenular functions are at least partly mediated by the complex network that links MHb/LHb with pontomesencephalic monoaminergic nuclei. Here, we summarize research about the topography and transmitter phenotype of the reciprocal connections between the LHb and ventral tegmental area‐nigra complex, as well as those between the LHb and DR/MnR. Indirect MHb outputs via interpeduncular nucleus to state‐setting neuromodulatory networks will also be commented. Finally, we discuss the role of specific LHb‐VTA and LHb/MHb‐raphe circuits in anxiety and depression. Abstract : Schematic diagram depicting major afferent and efferent connections of the habenula, highlighting its reciprocal connections with DA and 5‐HT cell groups and other state‐setting ascending neuromodulatory nuclei. There are two parallel output streams from the LHb to the VTA and DR: A relatively weak direct stream, primarily emanating from LHbM that targets VTA, DR, MnR and LDTg; and a more potent indirect stream via the RMTg to the VTA‐nigra complex and DR.